2013
DOI: 10.1111/liv.12238
|View full text |Cite
|
Sign up to set email alerts
|

Depending on the stage of hepatosteatosis, p53 causes apoptosis primarily through either DRAM‐induced autophagy or BAX

Abstract: Background & AimsApoptosis mediated by p53 plays a pathological role in the progression of hepatosteatosis. It is noteworthy that p53 can promote the expression of damage-regulated autophagy modulator (DRAM), an inducer of autophagy-mediated apoptosis. However, the relationship between p53-mediated apoptosis and autophagy in hepatosteatosis remains elusive. This study aimed to examine how p53 orchestrates autophagy and apoptosis to affect hepatosteatosis.MethodsHepG2 cells were treated with oleic acid (OA) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 39 publications
6
42
0
Order By: Relevance
“…30 Moreover, Liu et al found that the increased BAX level accelerates apoptotic death in severe fatty degeneration. 31 Similarly, our results showed that BAX was down-regulated in the NAFLD group. Furthermore, the IL-22 siRNA increased the expression of BAX, both in NAFLD cells and in a rat model under BP treatment.…”
Section: Papersupporting
confidence: 69%
“…30 Moreover, Liu et al found that the increased BAX level accelerates apoptotic death in severe fatty degeneration. 31 Similarly, our results showed that BAX was down-regulated in the NAFLD group. Furthermore, the IL-22 siRNA increased the expression of BAX, both in NAFLD cells and in a rat model under BP treatment.…”
Section: Papersupporting
confidence: 69%
“…DRAM is an inducer of autophagy-mediated apoptosis, and localization of DRAM in the mitochondria leads to autophagy (41). As an effector of p53-mediated apoptosis, DRAM is a p53 target gene inducing macroautophagy (34).…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Interestingly, DRAM/mitophagy signaling mediates apoptosis only in mild hepatosteatosis, whereas p53/BAX pathway induces apoptosis mainly in severe hepatosteatosis. 37 TNFa can induce autophagy in trophoblasts leading to the activation of apoptosis-intrinsic pathway. Knockdown of Atg5 prevents TNFa-dependent activation of proapoptotic caspases.…”
Section: Autophagy May Enable Apoptosismentioning
confidence: 99%